PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) DALAM UPAYA PENINGKATAN HASIL BELAJAR FIQIH SISWA DI KELAS II MADRASAH IBTIDAIYAH NEGERI 6 LANGKAT BOHOROK - Dahliana Dahliana (Universitas Negeri Medan, 2020)
Student learning outcomes by establishing a Team Games Tournament (TGT) Type Cooperative Learning Model have improved quite well. Before the class action (PTK) was carried out for the initial test, the average score of the Islamic Civilization History class II class II Madrasah Ibtidaiyah Negeri 6 Langkat Bohorok, which amounted to 31 students, was 70 (moderate category) and the standard deviation was 8,116. After the class action was carried out in cycle I for the first final test, the average score of Islamic Civilization History subjects increased to 74 (moderate category) and the standard deviation was 6.825. Followed by class action in cycle II for the second final test, the average value of Islamic Civilization History subjects increased to 80 (high category) and the standard deviation was 4.479 with a minimum completeness criteria value (KKM) of 65. Next, the correlation between the initial test and cycle I was 0.766. (quite significant category) with a t test value of 6.53, and the correlation between cycle I and cycle II was 0.95 (very significant category) with a t test value of 16.578. And before the action was carried out the average attendance rate of students was 80%, after the action was carried out in the first cycle it became 89%, in the second cycle it was 100%. In general, students learn to be more independent. Keywords: Classroom action research (PTK), Cooperative Learning Model Type Team Games Tournament (TGT), Student Islamic Civilization History Learning Outcomes